Benchmarking Quantum Chemical Methods: Are We Heading in the Right Direction? - Mata, Ricardo A. (Angew Chem Int Ed Engl, 2017)
Theoreticians and experimentalists should work together more closely to establish reliable rankings and benchmarks for quantum chemical methods. Comparison to carefully designed experimental benchmark data should be a priority. Guidelines to improve the situation for experiments and calculations are proposed.[Image: see text]